Simulation and Experimental Research on Tooth Power Skiving Cutting of Double-circular-arc Internal Gears - Wang Feng; Yang Shufeng; Xu Wenbo; Zhang Weijie; Yu Wentao (Jixie chuandong)
A method for machining double-circular-arc internal gears using power skiving technology is proposed to address the current problems of difficulty, poor accuracy, and low efficiency in machining double-circular-arc internal gears. Based on the principle of power skiving, the relative positions of the cutting tool and the workpiece are sorted out, and a mathematical model for double-circular-arc internal gear tooth turning is established. Vericut is used to simulate the formation of double-circular-arc tooth profiles, and the feasibility and accuracy of machining internal gears are verified. Abaqus is used to simulate and calculate the cutting force during the power skiving process, and the influence of machining parameters on the cutting force is obtained. Using a six-axis CNC machine tool, the power skiving of double-circular-arc internal gears is completed, and the tooth alignment accuracy detection meet the design requirements. This study expands the processing technology of double-circular-arc gears, improves the machining accuracy and efficiency of internal gears, and lays the foundation for future research on double-circular-arc internal meshing and planetary transmission.